Effective PHIP Labeling of Bioactive Peptides Boosts the Intensity of the NMR Signal1. Issue 47 (8th October 2014) - Sauer, Grit; Nasu, Daichi; Tietze, Daniel; Gutmann, Torsten; Englert, Simon; Avrutina, Olga; Kolmar, Harald; Buntkowsky, Gerd
Abstract A series of novel bioactive derivatives of the sunflower trypsin inhibitor‐1 (SFTI‐1) suitable for hyperpolarization by parahydrogen‐induced polarization (PHIP) was developed. The PHIP activity was achieved by labeling with L‐propargylglycine, O‐propargyl‐L‐tyrosine, or 4‐pentynoic acid. 1H NMR signal enhancements (SE) of up to a factor of 70 were achieved in aqueous solution. We found that an isolated spatial location of the triple bond within the respective label and its accessibility for the hydrogenation catalyst are essential factors for the degree of signal enhancement.